PROGRAMAS DE REDUÇÃO DE PESO VIA WEB: UMA REVISÃO - Camila Ragne Torreglosa; Andréa Polo Galante; Alexandre Rodrigues Lobo; Célia Colli (Universidade do Estado do Rio de Janeiro, 2014)
Introduction: The prevalence of obesity in the adult population is apublic health concern. Pharmacological, surgical and behavioraltherapies are consensual, but when they are not associated withchanges in lifestyle are often ineffective in the long term. Webprograms for weight loss are an alternative and complementary.Objective: To report web interventions for weight loss, analyze themodel of intervention and results in weight reduction. Methods:Only randomized clinical trials of nutritional intervention appliedvia web published between the years 2002 and 2012 were selected.Databases were MEDLINE via PubMed and Web of Science. Thearticles were evaluated by categories, being Category 1: objectives,study group, sample size, time, and loss of follow up; and Category2: intervention design, theoretical framework, personalizationstrategies and outcomes. Results: 15 randomized controlled trialswere selected. The personalization strategies have been preparedfrom information collected through questionnaires filled by theusers of programs. The interventions used models based ontheories of behavior. Reduction in body weight achieved in theweb groups ranged from 0.9 to 8.8 Kg. Conclusion: Web programsfor weight loss provide interaction among users and in some casespromotes weight reduction. However, the resources used are notdescribed in detail by the authors, and this hinders the creationof new science-based programs. DOI 10.12957/demetra.2014.6670